Pengaruh Pengelolaan Keuangan Daerah dan Sistem Pengendalian Internal Pemerintah terhadap Kinerja Pemerintah Daerah Kabupaten Bogor - Asep Asrudin Fiqri; Imelda Sari (Majalah Sainstekes, 2018)
The objectives of the research are to find out empirical evidence of the the effect of Local Financial Management and Internal Control System Government (SPIP) on Local Government Performance. This research was conducted at the Regional Device Work Unit (SKPD) in Bogor Regency, is West Bogor District. Each District of West Bogor taken three respondents namely the government, economic and administrative sections. The data used in this study is primary data obtained by distributing questionnaires directly to 41 respondents by using purposive sampling technique. Data analysis technique used in this research is Multiple Regression (Multiple Regression). The results of this study indicate that the Regional Financial Management and Government Internal Control System have a positive effect on the Performance of Local Government.